Determinants of Financial Performance in Interest-Free Microfinance Institutions: Evidence from Ethiopia - Ursad, Khalif Mohamed (IJIBE (International Journal of Islamic Business Ethics), 2025)
This study examines the determinants of financial performance in Interest-Free Microfinance Institutions (IMFIs) in Ethiopia. While Islamic finance has been recognized for promoting financial inclusion, limited research has addressed the performance and impact of IMFIs within the Ethiopian context. A longitudinal panel data approach was employed, using audited secondary data from three microfinance institutions offering interest-free services from 2012 to 2021. The study applied pooled Ordinary Least Squares (OLS) regression to evaluate the impact of internal and external factors on Return on Assets (ROA) as a performance metric. The empirical results reveal that institutional size has a statistically significant and positive impact on ROA. In contrast, operational efficiency, debt-to-equity ratio, and the number of active borrowers exhibit significant negative effects. Capital-to-asset ratio, institutional age, and GDP were found to be statistically insignificant. Accordingly, the study identifies debt-to-equity ratio, operational efficiency, number of active borrowers, and institutional size as key determinants significantly influencing the performance of interest-free microfinance institutions in Ethiopia. This research contributes to the literature on Islamic finance by providing novel insights into the performance drivers of IMFIs in an underexplored market. The findings offer valuable implications for policymakers and microfinance practitioners seeking to enhance the sustainability and impact of Shariah-compliant financial services in Ethiopia.